ADDRESSING EDUCATIONAL INEQUALITY: LITERATURE ANALYSIS AND IMPLEMENTATION STRATEGIES - Loso Judijanto; Al-Amin (Adisam Publisher, 2025)
Educational inequality is one of the major challenges faced by education systems in various countries. This article aims to explore and analyse the existing literature on educational inequality and formulate effective implementation strategies to address the problem. Through an in-depth literature review, it is found that educational inequality is caused by various factors, including economic, social, cultural and geographical differences. The research methodology includes qualitative analyses of case studies as well as evaluations of education policies that have been implemented in several countries that have been successful in achieving more equal education. Based on these findings, the article proposes a number of implementation strategies, such as increasing access to quality education, providing scholarships for underprivileged students, developing inclusive curricula, and equality-focused teacher training. The results of this study are expected to make a positive contribution to reducing educational inequalities and improving the sustainability of a fairer and more equitable education system.